Cerebral Near-Infrared Spectroscopy Monitoring and Neurologic Outcomes in Adult Cardiac Surgery Patients: A Systematic Review - Zheng, Fei; Sheinberg, Rosanne; Yee, May-Sann; Ono, Masa; Zheng, Yueyging; Hogue, Charles W. (Anesthesia and analgesia, 2013)
Near-infrared spectroscopy is used during cardiac surgery to monitor the adequacy of cerebral perfusion. In this systematic review, we evaluated available data for adult patients to determine (1) whether decrements in cerebral oximetry during cardiac surgery are associated with stroke, postoperative cognitive dysfunction (POCD), or delirium; and (2) whether interventions aimed at correcting cerebral oximetry decrements improve neurologic outcomes. We searched PubMed, Cochrane, and Embase databases from inception until January 31, 2012, without restriction on languages. Each article was examined for additional references. A publication was excluded if it did not include original data (e.g., review, commentary) or if it was not published as a full-length article in a peer-reviewed journal (e.g., abstract only). The identified abstracts were screened first, and full texts of eligible articles were reviewed independently by 2 investigators. For eligible publications, we recorded the number of subjects, type of surgery, and criteria for diagnosis of neurologic end points. We identified 13 case reports, 27 observational studies, and 2 prospectively randomized intervention trials that met our inclusion criteria. Case reports and 2 observational studies contained anecdotal evidence suggesting that regional cerebral O(2) saturation (rSco(2)) monitoring could be used to identify cardiopulmonary bypass cannula malposition. Six of 9 observational studies reported an association between acute rSco(2) desaturation and POCD based on the Mini-Mental State Examination (n = 3 studies) or more detailed cognitive testing (n = 6 studies). Two retrospective studies reported a relationship between rSco(2) desaturation and stroke or type I and II neurologic injury after surgery. The observational studies had many limitations, including small sample size, assessments only during the immediate postoperative period, and failure to perform risk adjustments. Two randomized studies evaluated the efficacy of interventions for treating rSco(2) desaturation during surgery, but adherence to the protocol was poor in one. In the other study, interventions for rSco(2) desaturation were associated with less major organ injury and shorter intensive care unit hospitalization compared with nonintervention. Reductions in rSco(2) during cardiac surgery may identify cardiopulmonary bypass cannula malposition, particularly during aortic surgery. Only low-level evidence links low rSco(2) during cardiac surgery to postoperative neurologic complications, and data are insufficient to conclude that interventions to improve rSco(2) desaturation prevent stroke or POCD.